Grenada : Interim Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2006)
This paper discusses the Interim Poverty Reduction Strategy Paper (I-PRSP) of Grenada for poverty reduction in the interim period. It describes the country's macroeconomic, structural, and social policies in support of growth and poverty reduction, as well as associated external financing needs and major sources of financing. It reviews the National Poverty Eradication Strategy and analyzes the monitoring indicators, risks and costing of the strategy. It assesses the national development plan aimed at attaining the Millennium Development Goals.